Smoking and gut microbiota: a cross sectional study involving students. (30th September 2020) - Cattaruzza, M S; Valeriani, F; Sindoni, A; Castrechini, M; Antinozzi, M; Romano Spica, V; Liguori, G; Galle, F
Abstract: Background: Cigarette smoking is associated with oncological and non-oncological diseases. Tobacco smoking causes more than 7 million deaths per year worldwide. Cigarette smoking could impact not only on human tissues and organs, but also on the gut microbiota, i.e. the community of microorganisms in the gastrointestinal tract. The aim of this study is to evaluate the composition of gut microbiota among smoker and non-smoker university students. Methods: Students from Sapienza University of Rome were asked to fill a questionnaire about smoking attitude and to provide a fecal sample. Students undergoing therapy which could affect gut microbiota were excluded. Differences in microbial composition and variability between smokers and non-smokers were assessed. Results: A total of 107 students (43.9% males, mean age 21.96±2.52 years, 30, 0% smokers) were enrolled so far. As for microbial composition, Firmicutes/Bacteroidetes ratios (F/B ratio) differed between smokers and non-smokers (5.34±16.66 vs 2.47±2.28). As for variability measures, smokers had lower Shannon index (3.43±0.26 vs 3.46±0.29). At Genus level, Prevotella was significantly more abundant in smokers (10.97±15.87 vs 4.86±10.86; p = 0.027) in comparison to non-smokers. Conclusions: Our preliminary results seem to suggest that smoking habit affects gut microbiota. Smokers had higher Firmicutes/Bacteroidetes ratio and Prevotella Genus, while lower Shannon index. These preliminary data suggest that smoking habit may cause changes in gut microbiota pattern, but further research is needed. Key messages: Smoking may cause changes in gut microbiota pattern. Smoking seems increases F/B ratio and Prevotella, while reduces gut microbiota variability.